Correlation Between Body Mass Index with Menstrual Cycle on Female Adolescent - Kumalasari, Mei Lina Fitri (International Conference on Sustainable Health Promotion, 2018)
Menstruation is the primary sexual sign that marks the period of puberty for women. Menstrual cycle disorders often occur in adolescents and are caused by several factors including psychological, hormonal, genetic disorders, organics abnormalities, and nutritional status. The nutritional situation is measured using a body mass index. The purpose of this study is to determine the correlation of body mass index and the menstrual cycle on the female adolescent. This research is an observational analytic study and uses a cross-sectional approach. The population of the study is all female students in Sunan Ampel State Islamic University. Accidental sampling technique is used in this study to obtain 36 respondent. Data collection from respondents was carried out by administering questionnaires and measurement of body weight and height. Data analysis uses the chi-square test. The result of the study is that most of body mass index (BMI) of respondents is standard (77,8%) and had regular menstrual cycles (75%). Chi-square test shows that there is a correlation between body mass index (BMI) and the length of the menstrual cycle (p=0,030).